Primary and Secondary Tethered Cord and Association with Pediatric Lower Urinary Tract Dysfunction - (:unkn) unknown (SPRINGER, 2019)
Purpose of Review Tethered cord syndrome (TCS) due to adhesion defect of the spinal cord is one of the major causes of lower urinary tract dysfunction (LUTD) in children. The aim of this article is to evaluate the association, diagnosis, and treatment of TCS with LUT disorders in children. Recent Findings TCS is divided into two groups as primary and secondary depending on whether it is congenital or acquired. TCS can manifest with gait disturbance, pain, orthopedic deformities, and LUT symptoms. LUT symptoms may be the only symptom in some cases. TCS may cause neurogenic LUTD characterized by detrusor sphincter dyssynergia, urinary incontinence, and upper urinary tract damage in children. Summary Primary urologic goal of surgical repair of TCS is prevention of upper urinary tract deterioration and improving LUT symptoms. Urodynamic studies revealing functional deterioration of the LUT are objective tests for surgical indication. Treatment should be planned by a multidisciplinary approach.
Keywords: Primary tethered cord syndrome; Secondary tethered cord syndrome; Neurogenic LUTD; Urodynamic studies; Multidisciplinary approach; OCCULT SPINAL DYSRAPHISM; URODYNAMIC FINDINGS; NEUROGENIC BLADDER; SURGICAL RELEASE; CONUS MEDULLARIS; CHILDREN; MANAGEMENT; PROGNOSIS; MYELOMENINGOCELE; MANIFESTATIONS